Partial nephrectomy without vessel clamping and hypothermia with conservative management of post-operative bleed in a rural setup: a case report - Goel, Tushar; Batra, Ravi; Sharma, Kamal (International Surgery Journal, 2017)
Hemorrhage is a well-known complication of partial nephrectomy. The bleeding is usually suspected when a patient presents with haematuria or bloody drain discharge following the procedure. This study’s primary objective is to discuss case of 63-year-old-man incidentally diagnosed with left lower pole kidney mass. USG abdomen was done and a suspicious mass in lower pole of kidney is noticed. CT-urography was done and assessment was made for further management. Patient details were collected by patient’s IPD file. Complete detailed history, patient vitals, hemogram, ABO, with USG abdomen and CT urography was done. Post op CT angiogram was done to evaluate for drain leak. Treatment diagnosis was left lower pole malignant mass. Pre-operative left ureteric catheter placement was done. 11th rib cutting incision was given. The tumour was resected with 1 cm margin. The renal defect was closed with interrupted sutures to the parenchyma. Gerota’s fascia was closed. A Robinson drain was placed and the abdominal wall closed. The case was managed without vessel clamping and hypothermia for clear renal cell carcinoma with post op bleed, successfully identified and managed conservatively, giving another potential management option in non-torrential haemorrhage.